Comparación de cinco dietas artificiales y una natural para la cría de larvas del barrenador del tallo, Diatraea saccharalis Fabr. - Calderón González, Katiuska Ninoska (2015)
Stalk borers have been a pest of greater importance in the cultivation of sugar cane in America. The species Diatraea saccharalis Fabricius remains one of the most damaging in the cultivation of sugarcane in the Ecuador. The production of Diatraea larvae on artificial diets, is a great alternative for the production of their natural enemies efficiently and with lower costs. This research Valdez, was carried out in the sugar mill in order to select a diet that meets nutritional requirements for the development of the larvae of the stem borer (Diatraea saccharalis). Five artificial diets were tested (diet Higsfeldt & Parra, Troncal La diet, diet diet Valdez 1 San Carlos and diet Valdez 2) and a natural diet (corn in corn State). For diets, each experimental unit consisted of a jar of 200 cc glass and natural diet a caramelero type of 4 l. capacity glass jar. 10 bottles in the case of diets and 10 corn were used as repetitions in the natural diet. A completely random design was used and for the comparison of means of the treatments was used the Tukey test, to the probability 0.05. According to the results, the natural diet (corn) presented best production rates of larvae of D. saccharalis, achieving greater recovery of larvae, higher larval survival and fewer days to fulfill its lifecycle, assessed two generations. Within the artificial diets, diets La Troncal and Valdez showed better performance, becoming a good alternative to obtain larvae of D. saccharalis, used in the production of parasitoids programs larval this pest.